BEYOND GUILTY PLEAS: THE PROCEDURALIZATION OF NEGOTIATED JUSTICE IN INTERNATIONAL CRIMINAL TRIBUNALS - Chiarini, Giovanni (Pravni zapisi, 2025)
Negotiated justice was first codified within the UN Ad Hoc Tribunals, where a consistent body of case law was developed. In contrast, plea-bargaining and guilty pleas were substantially denied in the earlier Nuremberg and Tokyo trials. The paper examines the theoretical and practical development of plea bargaining, tracing the proceduralization of negotiated justice in international criminal tribunals, which has ultimately resulted in the ICC’s abbreviated proceedings on an admission of guilt – a hybrid model incorporating features from civil law and common law systems, representing a compromise of Anglo-Saxon and European legal traditions. The paper also shows that at the ICC, the use of plea bargaining has reached an impasse, primarily due to two factors: its extremely limited application – reflected in only a single case to date – and unclear norms regarding the accused’s rights as well as the length of the proceedings.